(untitled) (Perner’s Contacts, 2011)
The paper contains descriptions of one possible approach of an identification of stochastically loaded structures. The purpose of this approach is to find an algorithm of a forecasting control of their working in real working conditions. It deals with a proposal of an application of vector time series moving average models (VARMA). Their parameters are possible to determine using the nonlinear modification of the least squares method. The paper contains a main theoretical principle of solved area and its application on a real testing structures. The main purpose of practical apllication is to identify the important parameters and to examine their relations to one another while gantry crane structure was modelled.